Combined MEK and VEGFR inhibition in orthotopic human lung cancer models results in enhanced inhibition of tumor angiogenesis, growth, and metastasis - Takahashi, O; Komaki, R; Smith, P; Jürgensmeier, J; Ryan, A; Bekele, B; Wistuba, I; Jacoby, J; Korshunova, M; Biernacka, A; Erez, B; Hosho, K; et al. (2012)
Purpose: Ras/Raf/mitogen-activated protein-extracellular signal-regulated kinase (ERK) kinase (MEK)/ERK signaling is critical for tumor cell proliferation and survival. Selumetinib is a potent, selective, and orally available MEK1/2 inhibitor. In this study, we evaluated the therapeutic efficacy of selumetinib alone or with cediranib, an orally available potent inhibitor of all three VEGF receptor (VEGFR) tyrosine kinases, in murine orthotopic non-small cell lung carcinoma (NSCLC) models. Experimental Design: NCI-H441 or NCI-H460 KRAS-mutant human NSCLC cells were injected into the lungs of mice. Mice were randomly assigned to treatment with selumetinib, cediranib, paclitaxel, selumetinib plus cediranib, or control. When controls became moribund, all animals were sacrificed and assessed for lung tumor burden and locoregional metastasis. Lung tumors and adjacent normal tissues were subjected to immunohistochemical analyses. Results: Selumetinib inhibited lung tumor growth and, particularly at higher dose, reduced locoregional metastasis, as did cediranib. Combining selumetinib and cediranib markedly enhanced their antitumor effects, with near complete suppression of metastasis. Immunohistochemistry of tumor tissues revealed that selumetinib alone or with cediranib reduced ERK phosphorylation, angiogenesis, and tumor cell proliferation and increased apoptosis. The antiangiogenic and apoptotic effects were substantially enhanced when the agents were combined. Selumetinib also inhibited lung tumor VEGF production and VEGFR signaling. Conclusions: In this study, we evaluated therapy directed against MEK combined with antiangiogenic therapy in distinct orthotopic NSCLC models. MEKinhibition resulted in potent antiangiogenic effects with decreased VEGF expression and signaling. Combining selumetinib with cediranib enhanced their antitumor and antiangiogenic effects. We conclude that combining selumetinib and cediranib represents a promising strategy for the treatment of NSCLC. ©2012 AACR.